PENGARUH VARIABEL EKONOMI MAKRO DAN FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 - 2019 (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2023)
This study aims to (1) determine the effect of inflation on stock prices in banking companies listed on the Indonesia Stock Exchange in 2015 – 2019; (2) Knowing the effect of Debt to Equity Ratio (DER) on stock prices in banking companies listed on the Indonesia Stock Exchange in 2015 – 2019; (3) Knowing the effect of Price to Book Value (PBV) on stock prices in banking companies listed on the Indonesia Stock Exchange in 2015 – 2019; (4) Knowing the effect of inflation, DER, PBV simultaneously on stock prices in banking companies listed on the Indonesia Stock Exchange in 2015 – 2019. The results of this study partially show that inflation has no effect on stock prices of banking companies listed on the Indonesia Stock Exchange in 2015 - 2019, partially showing that DER has an effect on stock prices of banking companies listed on the Indonesia Stock Exchange in 2015 - 2019, partially showing that PBV has no effect on stock prices of banking companies listed on the Indonesia Stock Exchange in 2015 - 2019, while the research results simultaneously show that inflation, DER, and PBV affect stock prices of listed banking companies on the Indonesia Stock Exchange in 2015 – 2019